2008
DOI: 10.1086/588727
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Relationship between Spiral Arm Morphology and Supermassive Black Hole Mass in Disk Galaxies

Abstract: We present a relationship between spiral arm pitch angle (a measure of the tightness of spiral structure) and the mass of supermassive black holes (BHs) in the nuclei of disk galaxies. We argue that this relationship is expected through a combination of other relationships, whose existence has already been demonstrated. The recent discovery of AGN in bulgeless disk galaxies suggests that halo concentration or virial mass may be one of the determining factors in BH mass. Taken together with the result that mass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
154
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 106 publications
(171 citation statements)
references
References 45 publications
16
154
1
Order By: Relevance
“…Furthermore, all relations used have weak points, such as the large intrinsic scatter of the FP-BH, the different regression slopes of the M BH − L sph relation (a consequence of the relatively small available galaxy sample in the low-mass end), and the lack of a robust physical interpretation of the M BH − PA relation. Additionally, the M BH − PA estimations may suffer from wavelength-dependent estimations of the pitch angle (see e.g., Grosbol & Patsis 1998;Martínez-García 2012;Martínez-García et al 2014, but also Seigar et al 2008;Davis et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, all relations used have weak points, such as the large intrinsic scatter of the FP-BH, the different regression slopes of the M BH − L sph relation (a consequence of the relatively small available galaxy sample in the low-mass end), and the lack of a robust physical interpretation of the M BH − PA relation. Additionally, the M BH − PA estimations may suffer from wavelength-dependent estimations of the pitch angle (see e.g., Grosbol & Patsis 1998;Martínez-García 2012;Martínez-García et al 2014, but also Seigar et al 2008;Davis et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…THE M BH -(SPIRAL ARM PITCH ANGLE) CONNECTION While the applicability of the M bh -M halo relation in lower mass spiral galaxies is unclear, there is a somewhat complementary relation which only operates in spiral galaxies. Seigar et al (2008;see also Ringermacher & Mead 2009;Treuthardt et al 2012 andBerrier et al 2013) have presented the relation between black hole mass and spiral arm pitch angle. The spiral arm pitch angle (e.g.…”
Section: Globular Cluster Systemsmentioning
confidence: 99%
“…Studies have shown that there is a correlation between the SMBH mass and a number of measurable features of the host galaxy due to the interaction between the SMBH and its surroundings. Some of the properties known to correlate well with the SMBH mass are the bulge luminosity (L Bulge ; Kormendy & Richstone 1995;Marconi & Hunt 2003), the bulge mass (M Bulge ; Kormendy & Richstone 1995;Marconi & Hunt 2003;Häring & Rix 2004), the mean velocity dispersion (σ) of the bulge stars (Ferrarese & Merritt 2000;Gebhardt et al 2000), the Sérsic index (n) of the majoraxis surface brightness profile , and the pitch angle (P ) of spiral arms in disk galaxies (Seigar et al 2008;Berrier et al 2013).…”
Section: Introductionmentioning
confidence: 99%